Learning, development, and home digital media use among 6 to 8 year old children - Johnson, Genevieve (Scientia Socialis, 2012)
Young school children commonly use a range of digital media technologies including television, video games, and the Internet. Parents of 40 children in first and second grade completed a questionnaire that queried: 1) demographics, 2) number of home digital media devices, and 3) extent and nature of child use of those devices. Teachers who taught these first and second grade students completed a rating scale on the school achievement and developmental ability of participating children. The pattern of correlations among measures of child achievement/ability and measures of teacher-reported internet literacy and parent-reported home digital media use suggests that internet use has many positive associations and that playing video games and watching television have some negative associations. For example, children’s mathematics skills were postively correlated with use of the Internet but negatively correlated with televsion viewing. In some cases, children who used the Internet alone appeared more competent than children who used the Internet with an adult. Digital media use during childhood is a complex phenonema with a range of potential outcomes. Simplistc approaches are counterproductive.